SUFISTIC APPROACH IN ISLAMIC EDUCATION - Zulfiana Herni; Junaidi; Ernaka Heri Putra Suharyanto (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2021)
AbsractIslamic education is essentially a process that is always associated with the values of vertical transcendence (piety). Therefore, the meaning of education is a combination of spiritual excellence and culture. In an effort to maximize the process of Islamic education, the learning process is carried out with a Sufistic approach. In a sense, it prioritizes the balance between intellectual, emotional and spiritual. The problem in this paper are what is the Sufistic approach? What are the core teachings of Sufism (Sufistic) in education? What are the sufistic roles in education as well as the Sufistic education paradigm towards the Islamic education process. The word Sufi is taken from the word suf which means wool or a more accepted opinion. By dressing modestly, they feel spared from riya' nature and show more zuhd. There are three points of Sufi teachings that can be developed in the world of education: Sufi Ahklaqi. Tasawuf Amali, Tasawuf Falsafi.